WACANA PENDIDIKAN MASYARAKAT DALAM NOVEL-NOVEL SASTERAWAN NEGARA ERA MILENIUM KETIGA DARI PERSPEKTIF REALISME LUKACS (Community Education Discourse in Novels of National Laureate of the Third Millenium Era from the Perspective of Lukacs’ Realism) - Asyraff, Jamin; Mary Fatimah, Subet (Penerbit Universiti Sultan Zainal Abidin, 2025)
The ongoing development of Malay literature has generated a line of remarkable authors in this country’s literary endeavors. The National Laureate award serves as an initiative toward establishing more outstanding authors as well as encouraging the production of quality works that may be taken as a guidance for the community in addressing today’s challenging daily issues. In keeping with the passage of time, this study analyses the novels of the third millennium era’s National Laureates, namely the novel Orang Kota Bharu (2003), Naratif Ogonshoto (2001), Delima Ranting Senja (2009), and Cengkaman Hasrat (2015), in order to identify thoughts or discourses that are relevant and significant to community education in this country as presented in their work. The method of content analysis of the novels studied was used in this qualitative study. The analysis is based on Lukacs’ (1963, 1978, 1898, 1990) realism perspective. Three objectives determined; to analyse the community education discourse presented in the National Laureates’ novels, to detail the relationship and impact of the National Laureates’ thoughts on community education, and to present the strengths, advantages, and significance of the National Laureates’ works on the development of society and the country. The findings of this study show that the novels studied contain thoughts that are relevant, significant and have an impact on community education in this country. The findings of this study additionally prove the strength, benefits, and significance of the National Laureates’ works on the development of society and the country.